Henricia pumila sp. nov.: A brooding seastar (Asteroidea) from the coastal northeastern Pacific - Eernisse, Douglas J.; Strathmann, Megumi F.; Strathmann, Richard R. (Zootaxa, 2010)
A small species of the seastar genus Henricia Gray, 1840 occurs along the cool temperate Pacific coast of North America from near Sitka, Alaska to just south of Ensenada, Baja California, Mexico. Its small adult size, mottled aboral colors, and benthic external brooding reproductive mode have long been noted, but it has never been formally separated from the larger, free-spawning Henricia leviuscula (Stimpson, 1857), with which it has been confused. Here we amplify the description of H. leviuscula, based on examination of the holotype and new specimens, and restrict it to only one of several similar species that co-occur in Puget Sound and vicinity. We also describe the small mottled brooder as Henricia pumila sp. nov., characterize its distribution, and contrast its morphology with H. leviuscula based on the arrangement of marginal plates and the microanatomy of aboral spines.